2023
DOI: 10.1038/s41523-023-00543-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune landscape of breast tumors with low and intermediate estrogen receptor expression

Abstract: Immune checkpoint blockade (ICB) is currently approved for patients with triple-negative breast cancer (TNBC), whereas responses to ICB are also observed in a small subgroup of Estrogen Receptor (ER)-positive breast cancer. The cut-off for ER-positivity (≥1%) is based on likelihood of endocrine treatment response, but ER-positive breast cancer represents a very heterogeneous group. This raises the question whether selection based on ER-negativity should be revisited to select patients for ICB treatment in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Similar to our findings, a recent study showed that ER Low Positive tumours were more frequently grade 3 and had a higher expression of Ki-67, compared to BCs with intermediate or high expression of ER [ 31 ]. Furthermore, they found that the expression of immune-related biomarkers in ER Low Positive was similar to that of ER-negative tumours.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, a recent study showed that ER Low Positive tumours were more frequently grade 3 and had a higher expression of Ki-67, compared to BCs with intermediate or high expression of ER [ 31 ]. Furthermore, they found that the expression of immune-related biomarkers in ER Low Positive was similar to that of ER-negative tumours.…”
Section: Discussionsupporting
confidence: 92%
“… 22 , 23 Furthermore, the degree of tumor infiltrating lymphocytes (TILs) in ER-negative and ER-low tumors seem to be the same with a high infiltration indicating that both groups are equally immunogenic. 10 , 24 Up to 15–20% of women with TNBC harbor a BRCA mutation, 25 , 26 and the incidence of BRCA 1/2 mutations seems to be at the same level in women with ER-low tumors. 27 …”
Section: Discussionmentioning
confidence: 99%
“…This is in line with accumulating evidence showing that ER-low/HER2-negative BC share similar molecular and immunological features and clinical behavior with ER-negative (0%) BCs. 60 , 61 , 62 , 63 Given that current eTNBC clinical trials investigating the use of new targeted agents such as immunotherapy are often limited to tumors with ER <1%, the inclusion of the ER low-positive subgroup in these trials is encouraged. 62 …”
Section: Discussionmentioning
confidence: 99%
“… 60 , 61 , 62 , 63 Given that current eTNBC clinical trials investigating the use of new targeted agents such as immunotherapy are often limited to tumors with ER <1%, the inclusion of the ER low-positive subgroup in these trials is encouraged. 62 …”
Section: Discussionmentioning
confidence: 99%